Commemoration of Durruti. Domenech is speaking. Behind him, f.l.t.r.: Garcia Oliver, Sanz, ?, Mas, Aldabaldetracu, ?. Copied from CNT collection
Commemoration of Durruti. Domenech is speaking. Behind him, f.l.t.r.: Garcia Oliver, Sanz, ?, Mas, Aldabaldetracu, ?. Copied from CNT collection.